2019
DOI: 10.1002/jctb.6276
|View full text |Cite
|
Sign up to set email alerts
|

Constructing the Pd/PdO/β‐Bi2O3 microspheres with enhanced photocatalytic activity for Bisphenol A degradation and NO removal

Abstract: BACKGROUND: Photocatalysis is one of the effective ways to solve the problem of water and gas pollution. An excellent photocatalyst should have the following advantages: efficient photocatalytic activity for gas and water pollutants, recyclable and stable characteristics, non-toxic and low-cost. Constructing heterojunctions and introducing oxygen vacancies (OVs) are two effective measures to achieve these targets. RESULTS: It is found that the 1.0% Pd/PdO/ -Bi 2 O 3 exhibits the best photocatalytic activity wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…In addition, Pd NPs were fabricated via ultrasonication of Andean blackberry leaf extract and were used for photocatalytic degradation of methylene blue. 23 Rao et al 24 reported enhanced photocatalytic degradation of bisphenol A by Pd/PdO/β-Bi 2 O 3 microspheres and M. A. Khan's research team 25 used guar gum as stabilizer to synthesize Pd NPs and applied the Pd NPs as catalysts for the degradation of azo dyes. However, these methods are complicated and difficult for synthesizing Pd NPs and some require sophisticated equipment.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Pd NPs were fabricated via ultrasonication of Andean blackberry leaf extract and were used for photocatalytic degradation of methylene blue. 23 Rao et al 24 reported enhanced photocatalytic degradation of bisphenol A by Pd/PdO/β-Bi 2 O 3 microspheres and M. A. Khan's research team 25 used guar gum as stabilizer to synthesize Pd NPs and applied the Pd NPs as catalysts for the degradation of azo dyes. However, these methods are complicated and difficult for synthesizing Pd NPs and some require sophisticated equipment.…”
Section: Introductionmentioning
confidence: 99%
“…The creation of O v defects and attachment of noble-metal nanoparticles can relax the above-mentioned problems. A ternary photocatalyst, Pd/PdO/β-Bi 2 O 3 , has been reported for BPA degradation by Zhu et al The microsphere photocatalysts were formed by assembling innumerable nanosheets. The improved light absorption of Pd nanoparticles, enhanced charge-carrier separation between PdO and a β-Bi 2 O 3 heterojunction, and Schottky contact between Pd and β-Bi 2 O 3 synergistically played important roles.…”
Section: Detoxification Of Edsmentioning
confidence: 99%
“…Chen et al, synthesized Bi-BiPO 4 nanocomposites through in situ solvothermal reduction for NO removal [52]. Rao et al, constructed Pb/PbO/β-Bi 2 O 3 microspheres for bisphenol A degradation and NO removal [53] and Wang et al, obtained three types of supported Cobalt catalysts (CoO x /SiO 2 , CoO x /Al 2 O 3, CoO x /TiO 2 ) for CO oxidation [54]. There are limited reports for metal titanates in degrading gaseous pollutants.…”
Section: Introductionmentioning
confidence: 99%